Telaah Komprehensif Jurnal: Pengujian Psikometri Skala Guttman untuk Mengukur Perilaku Seksual pada Remaja Berpacaran - Amin, Achmad Syaifullah (Maliki Interdisciplinary Journal, 2024)
This study aims to develop and test a Guttman-based psychometric scale to measure premarital sexual behavior in dating adolescents. Premarital sexual behavior, which includes touching, kissing, petting, and intercourse, is increasingly discussed in social and public health contexts in Indonesia. This study involved 657 adolescents aged 15 to 24 years from the Jakarta area and its surroundings. The Guttman Scale is used to measure the sequence of sexual behavior based on the level of intimacy. The results of the analysis show that the scale has high reliability with a Coefficient of Reproducibility (CR) of 0.946 and a Coefficient of Scalability (CS) of 0.756. Touching behavior is the most common, while intercourse is the rareest. The scale also shows significant gender differences, with adolescent boys scoring higher than adolescent girls. The study concluded that the Guttman scale is a valid and reliable tool for measuring premarital sexual behavior, providing important insights for the development of more effective sexual education interventions.